2018
DOI: 10.1097/ncc.0000000000000478
|View full text |Cite
|
Sign up to set email alerts
|

Comorbid Dementia and Cancer in Residents of Nursing Homes

Abstract: Background:Life expectancy is increasing continuously, which increases the likelihood of developing dementia or cancer. Both dementia and cancer are serious conditions that give manifold symptoms. The interaction of these conditions is however complex and less explored.Objectives:The aim of this study was to identify the prevalence of cancer and differences regarding neuropsychiatric symptoms (NPS) and medication among nursing home (NH) patients with and without dementia and cancer.Methods:This is a cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 43 publications
2
28
0
Order By: Relevance
“…Although the use of palliative care improved quality of death in patients with dementia, reduced quality of death in patients with dementia might reflect the challenges of providing care for cancer patients with dementia. Previous research showed that cancer patients with dementia displayed more agitation, apathy and sleep disturbances than those without dementia, and also indicated that cancer patients with dementia were given sedatives instead of necessary pain treatment . In the present study, pain was significantly associated with quality of life by the univariate analysis.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Although the use of palliative care improved quality of death in patients with dementia, reduced quality of death in patients with dementia might reflect the challenges of providing care for cancer patients with dementia. Previous research showed that cancer patients with dementia displayed more agitation, apathy and sleep disturbances than those without dementia, and also indicated that cancer patients with dementia were given sedatives instead of necessary pain treatment . In the present study, pain was significantly associated with quality of life by the univariate analysis.…”
Section: Discussionsupporting
confidence: 59%
“…Previous research showed that cancer patients with dementia displayed more agitation, apathy and sleep disturbances than those without dementia, and also indicated that cancer patients with dementia were given sedatives instead of necessary pain treatment. 23 In the present study, pain was significantly associated with quality of life by the univariate analysis. Pain is not only one of the most frequently encountered symptoms among patients with advanced illnesses, such as dementia and cancer, but it is also associated with lower quality of life.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Nursing home residents have complex physical and mental health problems, and are often prescribed numerous of medications [1,2]. In Norway, more than 80% of nursing home residents have mild to severe cognitive impairments [3,4]. It is acknowledged that polypharmacy often leads to medication-related problems (MRPs), and is further associated with hospitalizations, morbidity, mortality, and a decline in quality of life [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 46.8 million people worldwide suffer from dementia – a number estimated to reach 131.5 million by 2050 ( Prince et al, 2016 ). In nursing homes (NH), 50–80% of patients have dementia ( Helvik et al, 2015 ; Blytt et al, 2017b ), a neurodegenerative condition that results in the decline of physical and cognitive functions ( Cricco et al, 2001 ). Sleep disturbances are common among NH patients with dementia, with prevalence ranging from 24.5% ( Moran et al, 2005 ) to 60% ( Neikrug and Ancoli-Israel, 2010 ; Ownby et al, 2014 ; Peter-Derex et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%